Organizational culture in Qazvin hospitals (2013) - AM. Mosadeghrad (The Journal of Qazvin University of Medical Sciences, 2017)
Background: Organizational culture influences employees’ job satisfaction, commitment and performance. A strong corporate culture enhances organizational performance. Objective: The aim of this study was to determine the type of organizational culture in Qazvin hospitals. Methods: A descriptive and cross-sectional study was conducted by a survey questionnaire in Qazvin (2013) that was distributed among 800 hospital employees and managers based on stratified random sampling. Findings: The mean of hospitals’ organizational culture was 2.95 out of 5 score. Hospitals' organizational cultures were evaluated as strong in attention to details and stability dimensions and moderate in creativity, risk taking, team working and power distance dimensions. Attention to details in public hospitals was higher than private and social security hospitals. Conclusion: Organizational culture of Qazvin hospitals was evaluated as moderate. Managers for improving hospitals' performance and enhancing employees' and patients' satisfaction should create a culture of higher creativity, innovation, team working and risk taking and lower power distance.